2012
DOI: 10.1152/ajpendo.00198.2011
|View full text |Cite
|
Sign up to set email alerts
|

Amylin improves the effect of leptin on insulin sensitivity in leptin-resistant diet-induced obese mice

Abstract: improves the effect of leptin on insulin sensitivity in leptin-resistant diet-induced obese mice. Am J Physiol Endocrinol Metab 302: E924 -E931, 2012. First published January 24, 2012; doi:10.1152/ajpendo.00198.2011.-Leptin enhances insulin sensitivity in addition to reducing food intake and body weight. Recently, amylin, a pancreatic ␤-cell-derived hormone, was shown to restore a weight-reducing effect of leptin in leptin-resistant dietinduced obesity. However, whether amylin improves the effect of leptin on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
(60 reference statements)
4
15
0
Order By: Relevance
“…s5). Interestingly, lPEI-pcDNA3-IAPP polyplex also exhibited a greater reduction in both body weight and food intake, when compared to no treatment, lPEI-pcDNA3, or lPEI-pcDNA3-LEP treatment, which is consistent with the previous reports [8,9,33]. Additionally, the lPEI-pcDNA3-LEP group did not show a sharp dip in either weight or food intake due to the intrinsic LEP resistance in DIO mice [9,12].…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…s5). Interestingly, lPEI-pcDNA3-IAPP polyplex also exhibited a greater reduction in both body weight and food intake, when compared to no treatment, lPEI-pcDNA3, or lPEI-pcDNA3-LEP treatment, which is consistent with the previous reports [8,9,33]. Additionally, the lPEI-pcDNA3-LEP group did not show a sharp dip in either weight or food intake due to the intrinsic LEP resistance in DIO mice [9,12].…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…Consequently, given that insulin and amylin levels positively correlate (data not shown), our findings would suggest that elevated circulating amylin levels may be related to the increased insulin secretion observed as a compensation for decreased insulin action; however, the exact form of amylin (reduced, unreduced, or amylin acid) which could be responsible remains elusive. Consistent with our proposal, amylin can act as a neuroendocrine hormone that complements the effects of insulin in postprandial regulation and there is evidence that in mice amylin improves leptin-mediated increases in insulin sensitivity [25]. As seen with our results, the unreduced (biological active) form failed to correlate with hypertriglyceridemia, indicating the mechanisms by which elevated levels of amylin may affect insulin action are unknown.…”
Section: Discussionsupporting
confidence: 92%
“…The resistance towards leptin in this study was confirmed in a food intake test where leptin alone did not alter the food intake in HFD rats. This resistance to leptin was ameliorated by the treatment with KBP-042 as is also known from amylin treatment (Kusakabe et al, 2012). KBP-042 lowers food intake alone, however a clear potentiating effect was seen when the combination of the two peptides was given, and the lowered plasma levels of leptin also supports this.…”
Section: Leptin Resistance Is Reducedmentioning
confidence: 76%